Mechanical Bowel Preparation Is a Risk Factor for Postoperative Delirium as It Alters the Gut Microbiota Composition: A Prospective Randomized Single-Center Study - Yang, Zhoujing; Tong, Chuandi; Qian, Xinye; Wang, Hailian; Wang, Yingwei (Frontiers in Aging Neuroscience, 2022)
Background and Objective: Postoperative delirium (POD) is a frequent complication in patients undergoing gastrectomy. Increasing evidence suggests that abnormal gut microbiota composition may contribute to its morbidity. However, it is unclear whether mechanical bowel preparation would cause postoperative delirium by altering the patients’ gut microbiota. This study aimed to investigate the association between mechanical bowel preparation and postoperative delirium in patients undergoing gastrectomy. Methods: A prospective randomized single-center study was performed. A total of eighty-one patients with gastric cancer were enrolled and randomly assigned to two groups: preparation group and non-preparation group according to whether the patient received MBP before surgery. To diagnose postoperative delirium, we used the 3-Minute Diagnostic Interview for Confusion Assessment Method-defined delirium for five successive days after surgery. 16s rRNA gene sequencing was used to investigate changes in the intestinal bacteria. The Linear discriminant analysis (LDA) and effect size (LefSe) analysis were also used to identify the different taxa of fecal microbiota between the postoperative delirium and non-postoperative delirium groups . Results: We found that there was a significant difference in β-diversity of the gut microbiota between the preparation group and non-preparation group (P=0.048).Furthermore patients in the preparation group had a much higher rate of postoperative delirium (13/40, 32.5%) compared with that in non-preparation groups (4/41, 9.8%). Multivariate regression analysis adjusted by other risk factors indicated that mechanical bowel preparation was associated with the occurrence of delirium (odds ratio = 4.792; 95% confidence interval: 1.274-18.028; P=0.020). When comparing the gut microbiota of patients with and without POD, Bacteroides and Veillonella (genus), which were higher in the preparation group, were also higher in delirium patients (P＜0.05). Genus Olsenella was both relatively higher in the non-preparation group and non-POD group (P＜0.05). Conclusions: Mechanical bowel preparation not only altered the gut microbiota composition of patients with gastric cancer but also increased the incidence of postoperative delirium. Among all the gut microbiota altered by mechanical bowel preparation, Bacteroides and Veillonella genus might be a risk factor of POD.Genus Olsenella might be the beneficial bacteria to reduce the incidence of POD.